Feedback-feedforward control of offshore platforms under random waves. - Suhardjo, J. (Earthquake engineering & structural dynamics.)
This study investigates the control of jacket type offshore platforms. The deck displacement of jacket type offshore platforms can be controlled using both passive and active control mechanisms. Among the passive control mechanisms, a tuned mass damper concept is studied in this paper. Active control mechanisms considered here include the active mass damper, the active tendon mechanism and the propeller thruster. An optimal frequency domain approach to active control of wave excited platforms is used in which the H2 norm of the transfer function from the external disturbance to the regulated output is minimized. In this study, the hydrodynamic drag force is evaluated using the JONSWAP wave spectrum. Unlike conventional linearization approaches, the influence of non-linearity in the drag force is retained in this scheme by expressing the non-linear force components in terms of higher order convolutions of the water particle velocities. To demonstrate the effectiveness of this scheme, the platform performance with and without control devices under different sea states is evaluated. It is demonstrated that the control devices are useful in reducing the displacement response of jacket type offshore platforms, especially when the wave forces are concentrated at frequencies close to the natural frequencies of the platform. This becomes especially significant in deep waters because the natural frequencies of jacket type platforms fall closer to the dominant wave frequencies in deep waters. Adding control devices to deep water platforms will ensure a reduction both in the global response of the platform and in localized effects, such as the fatigue of welded joints.